Molecularly imprinted polymer membrane for the removal of naphthalene from petrochemical wastewater streams. Issue 6 (25th September 2017) - Ghasemi, Sahar; Nematollahzadeh, Ali
Abstract: The aim of this work was the preparation of molecularly imprinted membrane (MiM) using polysulfone (PSf) polymer for targeted removal of polycyclic aromatic hydrocarbons from petrochemical wastewater. Naphthalene was opted as a model pollutant, and the imprinted membrane was fabricated by phase inversion technique. Nonimprinted membrane (NiM) was also prepared in the absence of naphthalene and used as a reference. The polymers (MiM/NiM) were systematically characterized using different characterization techniques. The selectivity property of the membranes was evaluated by their ability in separation of naphthalene through filtration tests. Results showed that in comparison with NiM, the imprinted membrane exhibits higher affinity toward naphthalene molecules. It was found that the selectively of MiM is 2.27‐fold more than that of the corresponding NiM. This finding can be encouraging from industrial applications points of view.